Obsessive Compulsive Disorder As Seen In The Main Character Of Every Last Word Novel By Tamara Ireland Stone - Fitri Yani Yani; Samanik Samanik (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This research discusses a novel written by Tamara Ireland Stone entitled Every last word. This novel tells the story of Samantha as the main character who suffer Obsessive compulsive disorder in the novel. The author explain the condition of the main character Samantha who need to suffer with this mental issue, in Samantha’s daily activities the author describe the main character got the uncontrolled thought in her life, and she could not handle every details thought in her mind. This thesis has one research question: What is the symptom of Obsessive Compulsive Disorder as seen in the main character of Every Last Word novel by Tamara Ireland Stone.In this study, the writer uses descriptive qualitative methods to describe the phenomena inside the novel and supported by the quotation from the novel as the primary source. This thesis applies a psychological approach to describe the behavior of the main character that identified as the symptoms of obsessive compulsive disorder in Every last word by Tamara Ireland Stone. This thesis use Obsessive Compulsive theory In OCD there are several symptoms, such as: Unpleasant thought, feeling of doubt, inability to control the mind, fear of the bad thought and feeling of worry.This paper shows that the main character in Novel by Tamara Ireland Stone is clearly identified as person who suffered Pure Obsessive compulsive disorder, this seen by the daily activities, the main character shows the behavior that categorized as the symptoms of pure obsessive compulsive disorder. Key words : Every Last Word, Obsessive Compulsive Disorder, Tamara Ireland Stone